Analysis of expired medications in Serbian households - Paut Kusturica, Milica (Zdravstveno varstvo, 2016)
Introduction: An ongoing issue of expired medications accumulating in some households is a universal problem around the world. The aim of the study was to investigate the extent and structure of expired medications in Serbian households, and to determine which therapeutic groups generated the most waste. Methods: This was an observational, cross-sectional study conducted in households in the city of Novi Sad, Serbia. The study had been performed over 8 month period (December 2011 % July 2012) and it consisted of personal insights into the medication inventory in households. Results: Of 1008 families, 383 agreed to participate and complete the questionnaire (38.3% response rate). In almost a half of households (44.4%), expired medications were maintained. The amount of expired medications was 402 items, corresponding to 9.2% of total medications presented in surveyed households. The majority of expired medications (64.7%) was in solid dosage (tablets, capsules, granules, lozenges), following semisolid (ointments, creams, gel, suppositories) and liquid dosage forms (drops, syrups). Expired medications in the households belonged mostly to 3 categories: antimicrobials for systemic use (16.7%), dermatological preparation (15.9%) and medications for alimentary tract and metabolism (14.2%). Conclusions: This study revealed that there were relatively large quantities of expired medications in Serbian households, with a high prevalence of antibiotics for systemic use, anti inflammatory and antirheumatic products, and medications for alimentary tract and metabolism.
Keywords: drug; drug wastage; expired medications; gospodinjstva; households; rok uporabe; Serbia; Srbija; zdravila; zdravila s pretečenim rokom